Regional (dis)integration beyond governments: A comparison in social and civil society participation between Mercosur and SADC - Ramanzini Junior, Haroldo; Theodoro Luciano, Bruno [UNESP] (Center for International Area Studies, Hankuk University of Foreign Studies (Nurimedia Co., Ltd.), 2021)
The aim of this article is to analyse the involvement of civil society in regional integration organizations through a comparative analysis of social/civil society channels in the Southern Common Market (Mercosur) and the Southern African Development Community (SADC). We seek to analyse the level of openness and the trajectory of both blocs in relation to civil society participation. The instruments and strategies employed by civil society actors in both regions are contrasted, aiming to understand how prominent and successful they have been in terms of influencing the decision-making processes of Mercosur and the SADC, which have been traditionally marked by their intergovernmental and interpresidential characters. We argue that civil society involvement in regionalism is shaped by regional institutional design, member states’ support for societal participation and civil society resources. Thus, this article seeks to contribute to the comparative regionalism literature, setting out an analytical comparative framework for assessing the role of civil society in regional organizations from the Global South.
Keywords: civil society; comparative regionalism; Mercosur; Regionalism; SADC